Bromatologic composition of caged laying hen manure in different stocking periods - Oliveira, Mauro Dal Secco de; Vieira, Paulo de Figueiredo; Sampaio, Alexandre Amstalden Moraes (Pesquisa Agropecuaria Brasileira, 2014)
In this trial the chemical composition of caged laying hen manure was studied by means of a completely randomized design with four treatments and four replications. The treatment T1, T2, T3 and T4 consisted of manure stocked for 0, 14, 28 and 42-day periods respectively. Stocking period did not affect (P >0.01) crude fiber and ether extract levels of manure. Initial values of dry matter (DM), crude fiber (CF), crude protein (CP), ether extract (EE), nitrogen free extract (NFE), gross energy (GE), mineral matter (MM) and organic matter (OM) were 62.06%; 1 1.34%; 19.73%; 1.54%; 34.58%; 2,796.36 Kcal/kg of DM; 26.38%; and 73.61%, respectively. DM, CF, and MM increased 20.93%. (P<0.01); 20.02% (P>0.05); and 1.55% (P>0.05) and CP, EE, NFE, GE, and OM decreased 1.22% (P>0.05); 9.74% (P>0.05); 2.25% (P>0.05); 7.05% (P<0.01) and 0.55% (P>0.05), respectively, when manure was stocked for 14 days. Stocking for 42 days decreased DM, CP, MM, NFE, GE, and OM.